How Reliable, How Certain? A Bayesian Reliability Analysis of the Short Dark Tetrad (SD4) Among Indonesian University Students - Aflah Zakinov Irta; Rizal Kurniawan; Anindra Guspa (Nusantara Journal of Behavioral and Social Science, 2026)
The Dark Tetrad (subclinical narcissism, Machiavellianism, psychopathy, and sadism) is a central framework in personality psychology and is studied across clinical, organisational, and forensic contexts. The Short Dark Tetrad (SD4) has been adapted into several languages, but Indonesian studies have reported its reliability only as point estimates, without quantifying estimation uncertainty. This study therefore estimated the internal-consistency reliability of the Indonesian SD4 within a Bayesian framework. Responses from 289 Indonesian university students were analysed in JASP (1,000 MCMC samples; 50 burn-in) through a four-step sequence: MCMC trace plots, Posterior Predictive Check (PPP) eigenvalue plots, Bayesian single-factor fit diagnostics, and McDonald's ω posterior distributions with 95% Bayesian credible intervals (BCI). All chains converged, the eigenvalue evidence supported a dominant single factor (F1/F2 ratio = 2.5 to 3.6), and model fit was adequate to excellent (B-CFI = .905 to .965). Reliability was good for Sadism (ω = .813) and Narcissism (ω = .808) and acceptable for Machiavellianism (ω = .725) and Psychopathy (ω = .717). The Indonesian SD4 therefore shows acceptable-to-good internal-consistency reliability, reported here with explicit uncertainty and accompanied by a reproducible Bayesian reporting template. Because this evidence concerns reliability rather than validity, it supports research use in university-student samples, whereas high-stakes application will require further validity and measurement-invariance evidence. Abstrak: Dark Tetrad (narsisisme subklinis, Machiavellianisme, psikopati, dan sadisme) merupakan kerangka sentral dalam psikologi kepribadian dan dikaji pada konteks klinis, organisasi, serta forensik. Short Dark Tetrad (SD4) telah diadaptasi ke dalam beberapa bahasa, tetapi studi di Indonesia baru melaporkan reliabilitasnya sebagai estimasi titik tanpa mengukur ketidakpastian estimasi. Oleh karena itu, penelitian ini mengestimasi reliabilitas konsistensi internal SD4 versi Indonesia dalam kerangka Bayesian. Data dari 289 mahasiswa Indonesia dianalisis menggunakan JASP (1.000 sampel MCMC; burn-in 50) melalui empat langkah berurutan: plot jejak (trace plot) MCMC, plot nilai eigen Posterior Predictive Check (PPP), diagnostik kecocokan model faktor tunggal Bayesian, dan distribusi posterior ω McDonald beserta interval kredibel Bayesian 95% (BCI). Seluruh rantai konvergen, bukti nilai eigen mendukung satu faktor dominan (rasio F1/F2 = 2,5 hingga 3,6), dan kecocokan model tergolong memadai hingga sangat baik (B-CFI = 0,905 hingga 0,965). Reliabilitas tergolong baik untuk Sadisme (ω = 0,813) dan Narsisisme (ω = 0,808), serta dapat diterima untuk Machiavellianisme (ω = 0,725) dan Psikopati (ω = 0,717). Dengan demikian, SD4 versi Indonesia menunjukkan reliabilitas konsistensi internal yang dapat diterima hingga baik, dilaporkan disertai ketidakpastian yang eksplisit dan templat pelaporan Bayesian yang dapat direproduksi. Karena bukti ini menyangkut reliabilitas, bukan validitas, temuan ini mendukung penggunaan untuk keperluan penelitian pada sampel mahasiswa, sedangkan penerapan berisiko tinggi memerlukan bukti validitas dan invariansi pengukuran lebih lanjut.